2006
DOI: 10.1111/j.1365-3059.2006.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

An apparatus for collecting total conidia of Blumeria graminis f.sp. hordei from leaf colonies using electrostatic attraction

Abstract: Conidia from living conidiophores of barley powdery mildew ( Blumeria graminis f.sp. hordei ) on host leaves were collected consecutively using an electrostatic spore collector. The collector consisted of an electrical conductor plate linked to an electrostatic voltage generator and insulator plates placed abreast on a timed conveyer. The conductor plate was negatively charged by the potential supplied from the voltage generator. The negatively charged conductor plate caused dielectric polarization of the insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A physical method of excluding airborne fungal pathogens and flying pests from greenhouses with good air penetration involves forming an electrostatic barrier; this method reduces the use of agrochemicals such as fungicides and insecticides. The electrostatic method was initially devised to collect mature conidia on powdery mildew conidiophores (Moriura et al, 2006a(Moriura et al, , 2006bNonomura et al, 2009), and the first electrostatic spore precipitator was a screen that created a nonuniform electric field around insulated copper conductor wires arranged in parallel (Matsuda et al, 2006;Shimizu et al, 2007). This field generated an electrostatic force that attracted fungal conidia.…”
Section: Introductionmentioning
confidence: 99%
“…A physical method of excluding airborne fungal pathogens and flying pests from greenhouses with good air penetration involves forming an electrostatic barrier; this method reduces the use of agrochemicals such as fungicides and insecticides. The electrostatic method was initially devised to collect mature conidia on powdery mildew conidiophores (Moriura et al, 2006a(Moriura et al, , 2006bNonomura et al, 2009), and the first electrostatic spore precipitator was a screen that created a nonuniform electric field around insulated copper conductor wires arranged in parallel (Matsuda et al, 2006;Shimizu et al, 2007). This field generated an electrostatic force that attracted fungal conidia.…”
Section: Introductionmentioning
confidence: 99%
“…79,80 Our study showed successful electrostatic attraction of conidia to the probe tip; the works of electrostatic spore collection were published in some journals. [81][82][83] This finding was the start of our electric filed screen research. Hopefully, this force is available to the physical barrier for trapping air-borne conidia of fungal pathogens.…”
Section: Electrostatic Spore Collection Probe; An Original Invention mentioning
confidence: 82%
“…85 Powdery mildew conidia that came into this field also produce a dipole, and the opposite charges between the insulator and conidia create an electrostatic force. 81 This electrostatic force is applicable to collecting conidia released from colonies of barley powdery mildew infecting host leaves 82 and tomato powdery mildew. 83 Based on these electrostatic characteristics, a cylindrical electrostatic spore precipitator (SM-screen) has been developed to control conidia of tomato powdery mildew O. neolycopersici.…”
Section: Construction Of Discharge-generating Dipolar Electric Field mentioning
confidence: 99%
“…Applied electrostatic engineering has successfully managed pathogens and insect pests affecting agricultural crops at various stages of crop production and preservation. Electrostatic principles have been applied in diverse ways, including for capturing spores and insects by exploiting the attractive force generated in a static electric field (without electric discharge) (Matsuda et al, 2006;Kakutani et al, 2017;Nonomura et al, 2014a;Matsuda et al, 2012;Matsuda et al, 2011;Takikawa et al, 2015;Moriura et al, 2006aMoriura et al, , 2006bNonomura et al, 2009), repelling insects via their aversion to electric fields Matsuda et al, 2011;Matsuda et al, 2015b), disinfecting bacterial and fungal pathogens using ozone produced through streamer discharge (Shimizu et al, 2007), instantaneously dislodging fungal pathogens from plants through exposure to a plasma stream produced via a corona discharge in the electric field , instantaneously pulverizing insects nesting in dried rice grains (Matsuda et al, 2018c), electrocuting virus-carrying mosquitoes in the screen by insect-mediated arch discharge (Kakutani et al, 2018), and negatively ionizing smoke particles in the ionic wind produced during corona discharge (Matsuda et al, 2018b). In this work, we used electrostatic devices to repel and capture insect pests, creating a pest-free space in a greenhouse with open windows.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%